A study on the effect of different colours of culture tanks in nursery, on the production performance, biochemical composition of flesh and physiological responses of whiteleg shrimp (Litopenaeus vannamei). (16th April 2021) - Supriyono, Eddy; Rasul,; Budiardi, Tatag; Hastuti, Yuni Puji; Adiyana, Kukuh; Thesiana, Lolita
Abstract: Nursery is an effort to improve the quality and quantity of whiteleg shrimps ( Litopenaeus vannamei ) post‐larvae, before stocking in growth ponds. The objective of this research is to investigate the effect of coloured culture tanks on whiteleg shrimp production, performance and metabolic activities during nursery stage. The results showed that coloured culture tanks had no significant effect on their growth performance ( p > 0.05), but had significant effects on their survival rate (>72%) ( p < 0.05) and metabolic activities. Based on this research, the best colours for improving the survival rate and production performance of shrimps are green and blue.